Proceedings of the 2nd INDOEDUC4ALL - Indonesian Education for All (INDOEDUC 2018) 2018
DOI: 10.2991/indoeduc-18.2018.39
|View full text |Cite
|
Sign up to set email alerts
|

The Accessibility of Inclusive Schools in Surabaya

Abstract: Inclusive education is a form of education that is currently being implemented by the government in providing educational services for all children without any limitations or discrimination. Basically, inclusive education has a philosophy of education and social form. Inclusive education in Permendiknas No. 70 in 2009 is defined as an educational system that provides opportunities for all students with special needs and has the potential for intelligence and / or gifted to attend education or learning in an ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
1
0
4
Order By: Relevance
“…Pendidikan inklusi merupakan suatu pendekatan dalam pendidikan yang bertujuan untuk memastikan bahwa semua siswa, termasuk siswa dengan kebutuhan khusus, mendapatkan pendidikan yang sama dalam lingkungan yang inklusif. Pendidikan inklusi mempromosikan nilai kesetaraan, menghargai perbedaan, dan memperkuat keberagaman dalam lingkungan belajar (Irvan, M., & Jauhari, M. N. 2018). Dalam pendidikan inklusi, siswa dengan kebutuhan khusus diberi dukungan dan akses ke sumber daya yang dibutuhkan untuk memenuhi potensi mereka, sementara siswa yang lain juga belajar untuk menghargai keberagaman dan membangun keterampilan sosial yang positif (Rafikayati, A.…”
Section: Pendahuluanunclassified
“…Pendidikan inklusi merupakan suatu pendekatan dalam pendidikan yang bertujuan untuk memastikan bahwa semua siswa, termasuk siswa dengan kebutuhan khusus, mendapatkan pendidikan yang sama dalam lingkungan yang inklusif. Pendidikan inklusi mempromosikan nilai kesetaraan, menghargai perbedaan, dan memperkuat keberagaman dalam lingkungan belajar (Irvan, M., & Jauhari, M. N. 2018). Dalam pendidikan inklusi, siswa dengan kebutuhan khusus diberi dukungan dan akses ke sumber daya yang dibutuhkan untuk memenuhi potensi mereka, sementara siswa yang lain juga belajar untuk menghargai keberagaman dan membangun keterampilan sosial yang positif (Rafikayati, A.…”
Section: Pendahuluanunclassified
“…In Slovakia, narrow sidewalks and low-quality pavement surfaces were mentioned as physical environmental barriers, disabling PWDs' participation in green spaces (Halajova, 2016). Irvan and Jauhari (2018) found that even the inclusive schools in Indonesia were inaccessible to SWDs. PHUWs in main mosques in Riyadh-KSA faced many physical environmental barriers, revealing the need to reinforce accessibility policies (Abu Tariah et al, 2018), and the same was found in Accra-Ghana concerning Persons with mobility disabilities' daily experience (Naami, 2019).…”
Section: Improvement Of Pwds' Rights In Jordanmentioning
confidence: 99%
“…Implikasi dari pelaksanaan pendidikan inklusi ini adalah bahwa guru kini bertugas untuk bisa menyelenggarakan pembelajaran yang efektif dan efisien untuk populasi peserta didik yang beragam. Keberagaman itu meliputi peserta didik dengan gaya belajar dan kemampuan yang berbeda-beda, peserta didik yang memiliki keberagaman budaya dan bahasa, serta peserta didik yang berkebutuhan khusus seperti peserta didik tunanetra, tunarungu, tunadaksa, tunagrahita, autis, lambat belajar, memiliki kelainan perilaku, dan cerdas berbakat (Irvan, M., & Jauhari, M. N. 2018). Keadaan ini membutuhkan adanya strategi pembelajaran tertentu, dimana keberagaman karakteristik peserta didik tersebut dapat terakomodasi dalam sebuah lingkungan pembelajaran yang inklusif (Pérez-Gutiérrez, M., Castanedo-Alonso, J. M., Salceda-Mesa, M., & Cobo-Corrales, C. 2021).…”
Section: Pendahuluanunclassified